Penerapan Model Pembelajaran Discovery Learning Berbantuan Power Point Meningkatkan Hasil Belajar Siswa MTS Albadriyah Kupal Konsep Usaha dan Energi (International Forum of Researchers and Lecturers, 2024)
Physics learning contains concepts, applications and calculations and analysis may cause students find physics lessons difficult to be understood and will definitely affect the thinking ability of students in solving physics problems. To attract students' interest in learning, teachers should make learning activities more interesting with learning models and media that can encourage students' interest, so that the initial teacher-oriented learning activities become student-oriented learning activities. The aim of this study was to determine the increasing of students' learning in class VII MTs Albadriyah by implementing a discovery learning model using PowerPoint on the concepts of work and energy. This method of study is Classroom Action Research (PTK), the use of PTK is aimed to solve the problems found in the classroom. The result found that physics learning outcomes by applying discovery learning model on the concept of effort and energy in cycle I and cycle II. For cycle I the total number of students who completed learning was 6 students from 15 students or 40%. In cycle II, it increased to 11 of 15 students or 73%. The increasing in student learning activities in cycle I is 37.78% while in the cycle II it improved significantly to 83.89%. For the teacher's activity, there is an increasing of cycle I is 34.09% while in cycle II is 79.55%